Modelo termo-hidráulico em regime permanente para parte ativa de transformadores de potência validado por instrumentação óptica - Medeiros, Leonardo Hautrive (2023)
Due to the importance of the power transformer for electrical energy systems, designers are constantly looking for improvements in its thermal performance and, consequently, in prolonging its useful life. Since the composition of insulating paper is cellulose based, which has its aging and degradation accelerated under high temperatures during transformer operation, the paper becomes the dominant factor in its life expectancy. To keep temperatures within the limits stipulated by regulations, efficient thermal design and monitoring of operating conditions are necessary. In this sense, this work proposes a thermo-hydraulic model to determine the detailed distribution of the internal temperatures of power transformers’ active part in steady state. Based on transformer’s constructive dimensions and operational data, and with a fast processing response, the model builds networks of hydraulic and thermal resistances that, when coupled, determine: (i) the distribution of oil flows between the passage channels in the core and windings, and (ii) the distribution of temperatures in the oil channels, in the insulating paper and in the turns of winding discs, in addition to the temperature along the columns, yokes and joints of the magnetic core. The model is validated through temperature measurements using fiber optic sensors in temperature rise tests of a prototype transformer and a field transformer. Once verified its accuracy, the proposed model proves to be an accurate tool for determining and analyzing the hydraulic and thermal behavior of the active part of transformers. With generic modeling and simple application, the model meets the needs of the industry, being able to analyze the temperatures of transformers already in operation for the purposes of asset management and aid in decision making, as well as in the thermal design of new equipment, contributing to a reduction in costs, savings in materials and an increase in thermal performance, extending its useful life.